Fenomena Fatherless: Apakah ada Pengaruh Father Involvement Terhadap Self-Esteem Individu Dewasa Awal Fatherless di Kabupaten Karawang? - Salma Khonsya Assyfa; Wina Lova Riza; Dinda Aisha (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This research aims to determine the influence of father involvement on the self-esteem of early adult individuals in Karawang Regency. The method used in this research is a quantitative method, with a causality research design. The population in this study were early adults with an age range of 20-40 years according to the research criteria. The sampling technique used was convenience sampling technique and the number of respondents in this study was 141 respondents. The measuring instruments in this study used two psychological scales and a scale to measure father involvement using the Father Involvement Scale (FIS), and a self-esteem scale using the Rosenberg Self-Esteem Scale (RSES). The data analysis techniques used in this research are the normality test, linearity test, simple linear regression hypothesis test and additional tests, namely the coefficient of determination and categorization test. Based on the results of research that has been conducted, there is an influence of father involvement on the self-esteem of fatherless early adult individuals in Karawang Regency, with a regression significance value of 0.00. The coefficient of determination of father involvement on self-esteem is (R Square) 0.849 or 84.9%. So it can be said that the influence of father involvement on the self-esteem of fatherless early adult individuals in Karawang district is 84.9%, the rest is influenced by other variables which were not examined in this research.